THE IMPACT OF SALES PROMOTION AND CONSUMER TRUST ON STAYCATION INTEREST IN JAKARTA FOUR-STAR HOTEL DURING COVID-19 PANDEMIC - Ronny Yudhi Septa Priana; Tri Djoko Sulistiyo; Theresia Theresia (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The purpose of this study was to find out how the impact of Sales Promotion and Consumer Trust on Staycation Interest in Jakarta four-star hotel during Covid-19 pandemic. The research method used is descriptive quantitative research method using a sample of 100 respondents and 16 statements. Sales Promotion with a mean of 3.50 is in the very good category, Consumer Trust with a mean of 3.52is also in the very good category, and Staycation Interest with a mean of 3.36 is in the very high category. Sales Promotion has an effect on staycation interest by 16% and the remaining 84% is influenced by other variables not examined in this study. Consumer Trust has an effect on staycation interes by 43.5% and the remaining 56.5% is influenced by other variables not examined in this study. Sales Promotion and Consumer Trust have an influence on Staycation Interest by 45.1% and the remaining 54.9% is influenced by other variables not examined in this study.